TINGKAT PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN DIMEDIASI KEPUASAN PELANGGAN SOP SAUDARA TAMALANREA MAKASSAR - Reka Ruslan; Moch. Givan Andra Pratama; Andi Mappellawa; Hamri Hamri; Rifqah Ramdhana Jufri (Universitas Ichsan Sidenreng Rappang, 2026)
This study aims to analyze and determine the effect of service quality and product quality on customer loyalty, mediated by customer satisfaction at the SOP of Saudara Tamalanrea Makassar. This study employed a quantitative approach. Data collection involved distributing questionnaires to 100 respondents using purposive sampling. The data analysis technique used in this study was Partial Least Squares (PLS) with SmartPLS software as a supporting instrument. The results of this study indicate that service quality and product quality significantly influence customer loyalty. Customer satisfaction significantly influences customer loyalty. Service quality and product quality significantly influence customer satisfaction.